1941
DOI: 10.18241/0073-98552014731624
|View full text |Cite
|
Sign up to set email alerts
|

Óleo essencial de Rosmarinus officinalis L. como sanitizante natural para controle de bactérias sésseis em superfície utilizada para corte de alimentos

Abstract: Óleo essencial de Rosmarinus officinalis L. como sanitizante natural para controle de bactérias sésseis em superfície utilizada para corte de alimentos Essential oil of Rosmarinus officinalis L. as natural sanitizer for controlling the sessile bacteria and as antimicrobial on the food-cutting surfaces RESUMO Objetivou-se neste estudo determinar as concentrações mínimas inibitórias (CMI) e as concentrações bactericidas mínimas (CBM) pela técnica de macrodiluição em caldo do óleo essencial (OE) de Rosmarinus off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Due to the difficulties to reduce cells adhered to surfaces, new strategies for the biofilm control have been studied (Donlan, 2002), such as plants containing flavonoids that may break outer membrane and inhibit bacteria enzymatic activity (Nascimento et al., 2000). Recent studies have showed potential of some plant metabolites to reduce biofilm formation (Bazargani and Rohloff, 2016; Borges et al., 2014; Rocha et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulties to reduce cells adhered to surfaces, new strategies for the biofilm control have been studied (Donlan, 2002), such as plants containing flavonoids that may break outer membrane and inhibit bacteria enzymatic activity (Nascimento et al., 2000). Recent studies have showed potential of some plant metabolites to reduce biofilm formation (Bazargani and Rohloff, 2016; Borges et al., 2014; Rocha et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpenes preferentially tend to move from the aqueous phase towards the membrane structures, which results in their expansion, increased fluidity, and permeability; and then disrupting the embedded membrane proteins, altering the ion transport process, and inhibiting cell respiration. Therefore, the damage caused to the structure of the cytoplasmic membrane lead to impairment of functions such as site of enzymatic action, selective barrier, and energy generation (ONAWUNMI, 1989;TURINA et al 2006;VALERIANO et al, 2012;ROCHA et al, 2014).…”
Section: Cymbopogon Flexuosus Elionurus Latiflorusmentioning
confidence: 99%